Comparison of two external fixator systems for fracture reduction during minimally invasive plate osteosynthesis in simulated antebrachial fractures. Issue 7 (13th July 2017) - Gilbert, Erika D.; Lewis, Daniel D.; Townsend, Sarah; Kim, Stanley E.
Abstract: Objective: To compare the Minimally Invasive Reduction Instrumentation System (MIRIS) to a two‐ring circular fixator construct (CFC) for indirect reduction during minimally invasive plate osteosynthesis. Study Design: Cadaveric antebrachial fracture model. Animals: Ten skeletally mature dog cadavers. Methods: Simulated bilateral antebrachial fractures were reduced and stabilized with the MIRIS on one limb, and a CFC on the contralateral limb, prior to placing a 10 hole Locking Compression Plate. Time to satisfactory reduction and implant placement were compared. Difficulty of fracture reduction and plate application was subjectively scored (1 to 5) for each procedure. Prefracture and postoperative orthogonal antebrachial radiographs were compared to assess restoration of radial length and angulation in sagittal and frontal planes. A paired t test ( P ≤ .05) was used to compare parameters between the two reduction techniques. Results: Reduction was faster ( P = .0191) and plate application was subjectively easier ( P = .047) when using the MIRIS compared to the CFC. There were no differences in subjective difficulty of reduction or plate application time between techniques. Mean postoperative radial length was reduced by approximately 4‐mm, and procurvatum were decreased by approximately 7° compared to prefracture measurements, regardless of reduction technique. Conclusion: The MIRIS allowed for faster fracture reduction, and simplified plate placement compared to a temporary application of a CFC in our simulated antebrachial fracture model.